Do Alcohol Outlets Mediate the Effects of the Moving to Opportunity Experiment on Adolescent Excessive Drinking? A Secondary Analysis of a Randomized Controlled Trial. (15th October 2022) - Joshi, Spruha; Schmidt, Nicole M.; Thyden, Naomi H.; Glymour, M. Maria; Nelson, Toben F.; Haynes, David; Osypuk, Theresa L.
Abstract: Background: Housing mobility impacts adolescent alcohol use, and the neighborhood built environment may impact this relationship. Methods: Moving to Opportunity (MTO) was a multi-site, three-arm, household-level experiment. MTO randomly assigned one of three treatment arms (1994–1997) allowing families living in public housing to (1) receive a voucher to be redeemed any neighborhood (2) receive a voucher to be redeemed in a neighborhood with less than 10% poverty (3) remain in public housing (control). MTO decreased girls' alcohol use, but increased boys' alcohol use. Treatment groups were pooled because they are similar conceptually and statistically on our primary outcome. Among youth aged 12–19 in 2001–2002 (N = 2829), we estimated controlled direct effects mediation of MTO treatment effects on youth with housing vouchers (N = 1950) vs. controls (N = 879) on past 30-day number of drinks per day on days drank, using gender-stratified Poisson regression. Mediators were density of on- and off-premises alcohol outlets per square mile at the families' census tract of residence in 1997. Results: Treatment group youth were randomized to live in 1997 census tracts with lower off-premises, but higher on-premises, outlet density. MTO treatment (vs. controls) decreased drinking for girls via alcohol outlet density, but only at higher levels of outlet density. Treatment was 18% more beneficial when girls moved to high density neighborhoods, compared to controls who stayed living in public housing in high density neighborhoods. Conclusion: Additional social processes unmeasured in the current study may play an important role in the alcohol use and other health risks for girls.